(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This chapter deeply analyzes the epidemiology, pathological effects, and control strategies of parasites in birds. Based on existing scientific literature, the prevalence, types, and impact on bird health of endoparasites (e.g., coccidia, nematodes, cestodes, haemosporidian protozoa) and ectoparasites (lice, mites) are examined. Studies indicate that parasitic infections significantly affect bird survival, reproductive success, and migratory behavior, potentially posing zoonotic risks. Diagnostic methods and control measures are discussed, emphasizing the influence of global changes on parasite-host interactions. This analysis is crucial for avian health protection and conservation programs.